THE RELATIONSHIP BETWEEN DEPTH, N-BLOWS, AND SOIL BEARING CAPACITY BASED ON DYNAMIC CONE PENETROMETER (DCP) TESTING IN MURUNG RAYA REGENCY - Frans Putra Genesa; Nathanael Yanuar Kristianto; Lola Cassiophea; Muhtadin; Gagas Wira Syahputra (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2024)
This study investigates the relationship between depth, number of blows (N-Blows), and soil bearing capacity (Qall) using the Dynamic Cone Penetrometer (DCP) test at various locations in Murung Raya Regency, Central Kalimantan. Eight test sites were analyzed: DCP 06 and 07 in Muara Laung 2, DCP 08 and 09 in Batu Bua, DCP 10 and 11 in Mangkahui, and DCP 12 and 13 in Muara Bakanon. The study aimed to generate vital soil characteristic data to support safe and efficient foundation designs. Field testing involved recording N-Blows at specific depths and calculating Qall values, followed by linear regression analysis to evaluate relationships among these variables. Most locations demonstrated a strong correlation, with R² values exceeding 0.99. For instance, DCP 06, 07, and 10 recorded R² values of 0.998, 0.999, and 0.998, respectively, indicating highly reliable models. The highest accuracy was found at DCP 12 (R² = 1.000), while DCP 09 showed a lower R² value of 0.859, indicating potential variability in soil properties or external influences. Data visualization highlighted increasing trends in Qall and N-Blows with depth, reflecting stronger soil layers at greater depths. Design recommendations include shallow foundations for sites like DCP 06 and 07 (20–60 cm depth), while deep foundations are advised for DCP 09 and 13 to bypass weak upper layers. This research enhances understanding of soil behavior in Murung Raya, offering a robust framework for foundation planning and encouraging supplementary testing methods like the Standard Penetration Test (SPT) to refine findings further.